Muscle Flap Closures in Spine Surgery: Predictors of Usage Patterns and Factors Associated With Postoperative Complications From the NSQIP Database. Issue 1 (February 2022) - Price, Meghan J.; Tillis, Rose; Howell, Elizabeth P.; Ramirez, Luis; Dalton, Tara; Baëta, César; Mehta, Vikram; Abd-El-Barr, Muhammad M.; Karikari, Isaac O.; Goodwin, C. Rory; Brown, David A.
Abstract : Study Design: Retrospective cohort study using the National Surgical Quality Improvement Program. Objective: The objective of this study was to identify preoperative factors that impact the decision to perform prophylactic muscle flap closure and assess risk factors for wound healing complications in patients undergoing spinal procedures with and without muscle flap closure. Summary of Background Data: Prior studies suggest that muscle flap closure following complex spine surgery results in a lower risk of wound healing complications. However, these studies have been limited to single institutions and/or surgeons. Methods: The National Surgical Quality Improvement Program database was queried for all patients undergoing spine surgery between 2005 and 2017 with and without concomitant muscle flaps. Preoperative and perioperative variables were extracted. Univariate and multivariate analyses were performed to assess risk factors influencing surgical site infection (SSI) and wound disruption, as well as to delineate which preoperative factors increased the likelihood of patients receiving flap closures a priori . Results: Concomitant muscle flaps were performed on 758 patients; 301, 670 patients did not receive a flap. Overall 29 (3.83%) patients in the flap group experienced SSI compared to 5154 (1.71%) in the nonflap group ( P <0.0001). Preoperative steroid use [odds ratio (OR) 0.5; P <0.0001], wound infection (OR 0.24; P <0.0001), elevated white blood cell count (OR 1.034; P <0.0001), low hematocrit (OR 0.94; P <0.0001), preoperative transfusion (OR 0.22; P =0.0068) were significantly associated with utilization of muscle flaps. Perioperative factors including a contaminated wound (OR 4.72; P <0.0001), the American Society of Anesthesiologists classification of severe disease (OR 1.92; P =0.024), and longer operative time (OR 1.001; P =0.0024) were significantly associated with postoperative wound disruption. In addition, after propensity score matching for these factors that increase risk of wound complications, there was no difference in the rates of SSI between the flap and nonflap group. Conclusion: Our results suggest that patients with a higher burden of illness preoperatively are more likely to receive prophylactic paraspinal flaps which can reduce the rates of wound-related complications.